2017
DOI: 10.1088/1361-665x/aa5a5d
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of bimorph piezoelectric bending beams in energy harvesting applications

Abstract: Abstract.Piezoelectric energy harvesting is an attractive alternative to battery powering for wireless sensor networks. However, in order for it to be a viable long term solution the fatigue life needs to be assessed. Many vibration harvesting devices employ bimorph piezoelectric bending beams as transduction elements to convert mechanical to electrical energy. This paper introduces two degradation studies performed under symmetrical and asymmetrical sinusoidal loading. It is shown that besides a loss in outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…The four MFC piezoelectric beam specimens will be used for cyclic loading and actuation function degradation tests of cyclic loads with stress amplitudes 12 MPa, 18 MPa, 24 MPa and 30 MPa, respectively. The experimental results of the sensing function degradation test for the MFC sensor show that, when the MFC sensing function degradation degree is greater than 10%, which can be characterized by the reduction of its output voltage, it is considered that its function degradation is observable for the corresponding test case [12]. Hence, in the present test when the measured index A is greater than 90%, which indicates that the actuation function degradation degree is less than 10%, it will be considered that there is no actuation function degradation for the corresponding load cycles.…”
Section: Actuation Function Degradation Test Of Mfc Actuator Undergoimentioning
confidence: 99%
See 1 more Smart Citation
“…The four MFC piezoelectric beam specimens will be used for cyclic loading and actuation function degradation tests of cyclic loads with stress amplitudes 12 MPa, 18 MPa, 24 MPa and 30 MPa, respectively. The experimental results of the sensing function degradation test for the MFC sensor show that, when the MFC sensing function degradation degree is greater than 10%, which can be characterized by the reduction of its output voltage, it is considered that its function degradation is observable for the corresponding test case [12]. Hence, in the present test when the measured index A is greater than 90%, which indicates that the actuation function degradation degree is less than 10%, it will be considered that there is no actuation function degradation for the corresponding load cycles.…”
Section: Actuation Function Degradation Test Of Mfc Actuator Undergoimentioning
confidence: 99%
“…Based on experimental results, 600 µε was proposed to be the upper limit of safe strain amplitude for a reliable performance of MFC in the energy harvesting system. P. Pillatsch et al [12] investigated the degradation of bimorph piezoelectric bending beams under symmetrical and asymmetrical sinusoidal loading. It is concluded that the degradation of the bimorph piezoelectric patch will bring a loss in output power and the shift in resonance frequencies, and micro-cracking was shown to occur predominantly in piezoelectric layers under tensile stress.…”
Section: Introductionmentioning
confidence: 99%
“…Buckling of thin-walled composite beams under axial loads is also investigated [11]. It is shown that the pre-loading of the piezoceramic beams opens the opportunity for increased life time of devices in energy harvesting [12]. In the paper [13] it is reported that the preloading force need not to be constant; in the new types of magnetorheological elastomers for vibration isolators the magnetic attraction force is utilized to change the preloading.…”
Section: Introductionmentioning
confidence: 99%
“…An oscillating force was applied on the piezoelectric beams using direct impact generated by stoppers on a rotating host. A prototype with 12 bimorphs generated 10.2 mW at 6 Hz, but the direct impact is detrimental for the system stability and may cause material degradation …”
Section: Introductionmentioning
confidence: 99%
“…A prototype with 12 bimorphs generated 10.2 mW at 6 Hz, but the direct impact is detrimental for the system stability and may cause material degradation. [19] To avoid direct impacts, Khameneifar et al used the gravitational force of the tip mass on a PE beam to induce beam vibration from rotation. [20] The beam was mounted on a rotational host, whose rotational axis is perpendicular to the direction of gravity.…”
Section: Introductionmentioning
confidence: 99%